RISE: Issue and challenges of completing an international research grant: a reflection of the project on food security and sustainability / Assoc. Prof. Ts. Dr Abdul Rahman Saili - Saili, Abdul Rahman (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
The experience I have gained over the years in research writings and projects has earned me enough credit to be appointed as one of the Associate Professors at Universiti Teknologi MARA, Sarawak Campus. Such experiences were built on my interest in agribusiness and agriculture sustainability - two sub-areas in agriculture that I perceive as my research forte. With a strong research background and determination to explore further, I applied for the Sumitomo Foundation Grant, the first international grant under my belt, and succeeded on the first attempt. I am so blessed to have acquired the grant for the proposed project on Food Security and Sustainability: Exploring Malaysian and Japanese Youth Participation in Agriculture, which was completed successfully.